The impact of Knowledge transfer on the setting up and operating a Joint venture; A case study of Samsung Thales and Samsung Tesco - Kim, Jungmo (2008)
A Joint Venture (JV) is a new self-governing configuration created by the pooling of assets of two (or more) independent businesses for the sole purpose of achieving a specific outcome that would not have been achievable by any one of the firms alone (Kogut, 1988-a ; Robert, W. 2004). Transferring knowledge is one of the motivations to create new knowledge and innovations and it also provides competitive advantage to the firms (Inkpen, 2000). The purpose of this research is to prove that the motivation of knowledge transfer has a substantial impact on the setting up Joint venture and operating managerial and R&D strategy in JV. Two case studies were selected, Samsung Thales and Samsung Tesco both these JVÃÂÃÂ¢ÃÂÃÂÃÂÃÂs have achieved incredible success and growth over the10 years following the inception of the JV. In this research it was found that knowledge transfer as a strategic method is one of the most important motivations to set up joint venture in any industry. Moreover, another finding is that the transfer of knowledge not only has a strong impact on the management strategy and policy to build competitive advantage but also affects to create new managerial and R&D strategy in the newly formed joint venture. This work will be of interest both to those carrying out research into the setting up of JVÃÂÃÂ¢ÃÂÃÂÃÂÃÂs and to senior company executives considering a JV in Asia.